Reporting local cultures in the globalised world: how indigenised can English be in the free world?. Issue 2 (August 2022) - Ali, Sadia; Thompson, Paul
Abstract : This paper presents a corpus-based analysis of English newspaper reportage in two South Asian countries, Pakistan (where English was introduced through colonisation) and Afghanistan (which has not been colonised), and their comparison with British newspaper reportage. The objective of this study is to analyse linguistic variation between the cultural press reportage (cpr ) of the selected countries and to see which variety of English, Pakistani or Afghan, resembles British English the most. To achieve this objective, three English newspapers from each country were selected for the compilation of a specialised corpus which was analysed with reference to the five textual dimensions introduced by Biber (1988, 2006 ). This research is significant as no previous study has attempted to find the differences and similarities between the Englishes used in a formerly colonised country and a country that was never part of the British Empire. The comparison indicates that Pakistani cpr is close to British cpr, while Afghan cpr is different. In terms of Biber's five textual dimensions, Afghan cpr is more informational, narrative, explicit and abstract, and less non-argumentative in comparison with British and Pakistani cpr .